Automatización del proceso de engrasado de las bandejas de pan en la línea de bollería - Barrantes-Domínguez, Raúl (Instituto Tecnológico de Costa Rica, 2001)
Is had that the part of the fattened of the trays of bread is an important process within the elaboration of the products of the company Panificadora BIMBO from Costa Rica, due to that subsequently this products pass to the process of baking and of not working hard the fat in the molds the mass of the bread well it could come to stick in these. At this time in the line of bollería are carried out this process of manual form by means of some mouthpieces of due application to that the machine of fat DUBOR installed in this line was harmed, this reason permits that it wear out more fat of the necessary due to that it work hard of a more abundant form and also of a form less uniform. The expense of this fat, economically, is considerable, for this reason it analize the possibility of automating this process by means of the use of a controller (PLC) since the person could program of several forms searching for the more appropriate for the required process. A PLC of the ALPHA series of due Mitsubishi to their characteristics was utilized since it could carry out this task satisfactorily, for their comfortable cost, in comparison to another, and for the ease that introduced the software to the hour of carrying out the program. By means of a vicinity sensor a characteristic of the molds of bread was taken advantage of: the cavities; it thanks to these is that one could establish the moment of dispersion of the fat for each mold, this due to that several types of mold for several types of bread exist, for this reason is that it was utilized the PLC, by means of this one could program several processes according to a selection that it are carried out previous. With everything are controlled it a “electroválvula” that permits the pass of air toward the mouthpieces that they finally carry out the dispersion of the fat. The realization of this project permits to the company save 40% of the fat utilized before the automation, with which, this calm justified project since the company benefits economically, as well as with the quality of the product final.
Proyecto de Graduación (Licenciatura en Ingeniería Electrónica) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería Electrónica, 2001.
Keywords: Software; Hardware; Sensores; Moldes; Procesos